Different durations within the method of best practice affect the parameters of the speed-duration relationship - Triska, C.; Karsten, B.; Beedie, C.; Koller-Zeisler, B.; Nimmerichter, A.; Tschan, H. (European Journal of Sport Science, 2018)
The aim of the study was to determine whether estimates of the speed-duration relationship are affected using different time-trial (TT) field-based testing protocols, where exhaustive times were located within the generally recommended durations of 2-15 min. Ten triathletes (mean ± SD age: 31.0 ± 5.7 years; height: 1.81 ± 0.05 m; body mass: 76.5 ± 6.8 kg) performed two randomly assigned field tests to determine critical speed (CS) and the total distance covered above CS (D´). CS and D´ were obtained using two different protocols comprising three TT that were interspersed by 60 min passive rest. The TTs were 12, 7, and 3 min in Protocol I and 10, 5, and 2 min in Protocol II. A linear relationship of speed vs. the inverse of time (s = D´ × 1/t + CS) was used to determine parameter estimates. Significant differences were found for CS (p =0.026), but not for D´ (p = 0.123). The effect size for CS (d = 0.305) was considered small, while that for D´ was considered moderate (d = 0.742). CS was significantly correlated between protocols (r = 0.934; p < 0.001), however, no correlation was found for D´ (r = 0.053; p = 0.884). The 95% limits of agreement were ±0.28m s-1 and ±73.9 m for CS and D´, respectively. These findings demonstrate that the choice of exhaustive times within commonly accepted durations results in different estimates of CS and D´, and thus protocols cannot be used interchangeably. The use of a consistent protocol is therefore recommended, when investigating or monitoring the speed-duration relationship estimates in well-trained athletes.